2020
DOI: 10.3390/ijms21031048
|View full text |Cite
|
Sign up to set email alerts
|

The Intravitreal Injection of Lanosterol Nanoparticles Rescues Lens Structure Collapse at an Early Stage in Shumiya Cataract Rats

Abstract: We designed an intravitreal injection formulation containing lanosterol nanoparticles (LAN-NPs) via the bead mill method and evaluated the therapeutic effect of LAN-NPs on lens structure collapse and opacification using two rat cataract models (SCR-N, rats with slight lens structure collapse; SCR-C, rats with the combination of a remarkable lens structure collapse and opacification). The particle size of lanosterol in the LAN-NPs was around 50–400 nm. A single injection of LAN-NPs (0.5%) supplied lanosterol in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…A greater supplement of Lan content may be needed to reverse crystallin aggregation and restore transparency to opaque lens. Moreover, we previously reported that the serious structural collapses with posterior movement of the lens nucleus were observed in the SCR-C [ 24 ], and the serious structural collapses was not reversed by the instillation of LA-NPs/ISG in this study. Further studies are needed to investigate whether the treatment of Lan can restore opaque lenses to transparency.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…A greater supplement of Lan content may be needed to reverse crystallin aggregation and restore transparency to opaque lens. Moreover, we previously reported that the serious structural collapses with posterior movement of the lens nucleus were observed in the SCR-C [ 24 ], and the serious structural collapses was not reversed by the instillation of LA-NPs/ISG in this study. Further studies are needed to investigate whether the treatment of Lan can restore opaque lenses to transparency.…”
Section: Discussionmentioning
confidence: 51%
“…Twenty microliters of samples in methanol were injected, and the Lan in samples was separated by an LC-10AD pump (Shimadzu, Kyoto, Japan) with TSK gel ODS-100S (5 µm, 150 × 2.0 mm I.D., Tosoh Co., Tokyo, Japan), a step gradient experiment was performed using 5% and 100% methanol over 19 min (flow rate of 0.4 mL/min), and the Lan was detected by a Corona Veo detector (Thermo Fisher Scientific, Inc., Waltham, MA, USA). The charger voltage, charger current, and inlet pressure (nitrogen) were 2.66 kV, 0.99 µA, and 61.9 psi, respectively [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…Recently, it has also been reported that lanosterol plays a preventive role in cataract formation, inhibiting lens opacity and reversing crystalline aggregation [18]. Additionally, intravitreal injection of lanosterol nanoparticles has been reported to rescue early stage of lens damage in SCRs [7]. Thus, synthesis of cholesterol by LSS is important to maintain lens transparency.…”
Section: Discussionmentioning
confidence: 99%
“…It promotes cell apoptosis and senescence and is also associated with many diseases [5,6]. Oxidative stress and reactive oxygen species (ROS) are a major cause of age-related eye diseases, and diets rich in fruits, vegetables, vitamin C, zeaxanthin, lutein, and multivitamin-mineral supplements are recommended for cataracts and age-related macular degeneration (AMD) [7][8][9][10]. Moreover, several risk factors such as advancing age, genetic predisposition, oxidative stress and external and internal factors causing adversely on lens homeostasis have been implicated to contribute to the etiology of cataract formation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation